Critical choices the United Nations, networks, and the future of global governance - Reinicke, Wolfgang H.
The new global environment requires new approaches, new ideas and innovative tools to address new challenges in areas as different as weapons control, climate change, genetic engineering, and labor standards. Critical Choices looks at one such tool: global public policy networks. In these networks, governments, international organizations, the corporate sector and civil society join together to achieve what none can accomplish on its own. The authors explore both the promises and the limitations of this new form of global cooperation. They discuss how such networks might contribute to better manage the risks and make use of the opportunities that globalization presents. Finally, they offer provocative advice and solid recommendations on how the United Nations can foster such networks in the years ahead.